Social sciences in sport - Maguire, Joseph (Human Kinetics, 2014)
Social Sciences in Sports presents discipline-specific knowledge in the social sciences, aiding in understanding the problems and potential of contemporary sport practices and experiences. This interdisciplinary reference provides in-depth coverage of sport studies and 14 social sciences, drawing connection across these disciplines to illuminate key issues and illustrate possibilities for change. Editor Joseph Maquire and an esteemed team of contributors synthesize theory and research in the area of social science and sport with special attention to four distinct topics: identity, community, capital, and governance